Capsaicin’s Inhibition Effects on Biofilm Aerococcus Viridans - Fery Setiawan1 , Jenny Sunariani2 , Ahmad Yudianto3 , Latief Mooduto4 , Eta Radhianto5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Aerococci has colony shape with Streptococcus viridans, so that it is usually missdiagnosed between of them. It has high difficulty on its identification, because it is rarely to be found and resistant of Antibiotic grup, called penicilin and vancomycin. Material and Method: This research used two kinds of samples, such as: fried food sold on the road and toothbrush obtained from ten respondens. Then, it needs inducing its biofilm and measuring by Tissue Culture Plate (TCP) methode and ELISA. Result: ANOVA one-way revealed that extract capsaicin has anti biofilm effect on 12.5% concentration with p=0,0000 (p<0,05) among each group. Conclusion: Extract capsaicin can be used as an alternative herbal agent to treat infection caused by Aerococcus viridans because it has antibiofilm effect. As known before, biofilm causes antibiotic resistance to treat Aerococcus viridans’s infection.